Exploring the Link between Periodontal Disease and Systemic Conditions: Implications for Alzheimer’s, Parkinson’s, and Rheumatoid Arthritis - Kanimozhi; K. Aishwarya; Sweta Yadav; Ajith A. Chandy; Ramyashri Muralikrishna; Rohan Shinkre (Journal of Pharmacy and Bioallied Sciences)
Background: There is a growing correlation between periodontal disease, a common inflammatory disorder that affects the tissues supporting the teeth, and several systemic diseases. Materials and Methods: Two hundred patients from a tertiary care hospital, ages 50–75, participated in this cross-sectional research. The subjects were split up into four groups: 50 individuals with rheumatoid arthritis, 50 with Alzheimer’s disease, 50 with Parkinson’s disease, and 50 with periodontal disease. To evaluate periodontal condition, including clinical attachment loss and pocket depth, thorough oral exams were performed. Measurements were made of serum biomarkers for inflammation, such as interleukin-6 (IL-6) and C-reactive protein (CRP). Multivariate regression models were used to examine correlations between the severity of periodontal disease and the underlying systemic diseases. Results: In all groups, there were significant relationships between higher levels of indicators of systemic inflammation and the severity of periodontal disease. In comparison to healthy controls (CRP mean value: 2.1 mg/L; IL-6 mean value: 6.4 pg/mL), participants with periodontal disease had higher mean levels of CRP (5.6 mg/L) and IL-6 (mean value: 12.8 pg/mL). Furthermore, compared to those with rheumatoid arthritis, those with Alzheimer’s and Parkinson’s disorders showed higher levels of pocket depth and periodontal attachment loss. Conclusion: In conclusion, the results point to a possible connection between systemic diseases such rheumatoid arthritis, Parkinson’s disease, and Alzheimer’s.